ANALISIS SISTEM PENGENDALIAN INTERN KAS PADA SEKOLAH TINGGI ILMU KEPERAWATAN (STIK) MUHAMMADIYAH PONTIANAK - B51109104, Fitrianti Rezeki (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Cash is one of the assets that has an important role in an institution and institutional management in both the services and trading company. Cash is important as it is the most liquid assets. In an effort to protect the cash from theft and misuse, an agency must has a cash internal system control over acceptance to outlay process. STIK Muhamamadiyah Pontianak is a private services institute. In the implementation of operational activities always have cash transaction. Therefore, STIK Muhammadiyah requires a procedure of internal control of cash receipts and disbursements. By its systems and procedures can be seen the movement of entry and exit of cash and control of cash can take place properly.   This study aims to determine how the internal cash system control of STIK Muhammadiyah  Pontianak. The research method used descriptive analysis.   The results showed that the internal control system of cash receipts was effective, since most revenues of semester fee through banks, so that the recording could be controlled through newspaper accounts, and reduce the risk of errors reception. The system of internal control cash disbursements  also  quite effective even though there were some weaknesses because  elements of internal control in the institutions have not been fully carried out, among others, improve the effectiveness of the system of petty cash (petty cash), there were still large amounts paid cash for reasons of practicality, the procedure has been made but sometimes  often overlooked,  unimplemented punishment of a sense of tolerance. Authorization system has been well perceived because of the separation the functions that involved multiple parts in which the system of cash receipts and disbursements more accurate monitoring and small fraud.   Keywords: internal control system, cash.